Environmental regulation, comparative advantage and the Porter hypothesis - Johan Albrecht (Fondazione Eni Enrico Mattei (FEEM), 1998)
Empirical surveys find no significant impact of environmental regulation and environmental costs on international competitiveness. In the literature, we can find three hypotheses on the impact of environmental regulation. For the industrial-flight and pollution-haven hypothesis, there is no clear empirical evidence. We show that this is a logical consequence of the principle of comparative advantage. Another explanation can be that developed countries have very diversified exports and most surveys do not link regulation to specific products. We therefore investigate the link between export diversification and two measures of labour productivity. The Porter hypothesis - the third or revisionist hypothesis in our overview - states that environmental regulation can lead to improved competitiveness. Many authors only find 'anecdotal' evidence for this hypothesis but we show that when regulation is linked to specific products, there is clear evidence for the Porter hypothesis. In our model, we work with international CFC-regulation (chlorofluorocarbons) and the export performance of CFC-using industries like refrigerators, freezers and air conditioning machines. A final section does focus on the tradition of cartelization that has been typical in many of the old - and 'dirty' - industries.
Keywords: F14; F21; L52; O32; Q28; 330; Environmental regulation; Industrial flight; Comparative advantage; Export diversification; Porter hypothesis; Umweltstandard; Internationaler Wettbewerb; Komparativer Vorteil; Exportdiversifizierung; FCKW; Standortfaktor; Theorie; Welt